Pengaruh Perkembangan Teknologi di Era Digital terhadap Investasi dan Pasar Modal - Sidayang, Stince; Allo, Mayke Hermalisa Turu’; Tiwa, Andro Stevano; Pangemanan, Novrita; Harefa, Juniman Pasrah; Abner, Abner (Fakultas Ilmu Sosial dan Hukum, 2024)
This research aims to analyze the impact of digital technology developments on investment and financial markets. The method used is normative legal research, with data collection through literature study. The analysis evaluated how technology, such as online trading platforms and trading algorithms, impacts investor accessibility and transaction efficiency. The research results show that technological advances have increased investor participation and market transparency, but have also created new challenges related to regulations that are not yet fully responsive to innovation. Therefore, policy changes are needed to create a safe investment environment and support innovation.